2005
DOI: 10.2139/ssrn.803649
|View full text |Cite
|
Sign up to set email alerts
|

Trends in U.S. Wage Inequality: Re-Assessing the Revisionists

Abstract: A large literature documents a substantial rise in U.S. wage inequality and educational wage differentials over the past several decades and finds that these trends can be primarily accounted for by shifts in the supply of and demand for skills reinforced by the erosion of labor market institutions affecting the wages of low-and middle-wage workers. Drawing on an additional decade of data, a number of recent contributions reject this consensus to conclude that (1) the rise in wage inequality was an "episodic" … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
142
0
11

Year Published

2008
2008
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 99 publications
(159 citation statements)
references
References 40 publications
(99 reference statements)
6
142
0
11
Order By: Relevance
“…Alternatively, for a given circumstances group it is possible to observe more earnings variation, since effort differences are defined by within group inequality. Since Juhn et al [23] these kinds of phenomena have been much discussed in the literature, it is nowadays commonly admitted that within-group inequality represents a large share of earnings inequality growth, see Lemieux [27] or Autor et al [5] for recent assessments.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Alternatively, for a given circumstances group it is possible to observe more earnings variation, since effort differences are defined by within group inequality. Since Juhn et al [23] these kinds of phenomena have been much discussed in the literature, it is nowadays commonly admitted that within-group inequality represents a large share of earnings inequality growth, see Lemieux [27] or Autor et al [5] for recent assessments.…”
Section: Resultsmentioning
confidence: 99%
“…The Theil index growth rate from 1980 to 2001 is around 79% (from .13 in 1980 to .24 in 2001). However, during the second half of the nineties the growth of earnings inequality is weaker before increasing over the last few years of the sample as described by Lemieux [27], Autor et al [5] and Gottschalk and Danziger [19].…”
Section: Changes In Earnings Inequality: 1968-2001mentioning
confidence: 89%
See 2 more Smart Citations
“…Although Korea provides the National Health Insurance (NHI), providing universal health insurance coverage to all citizens, its benefit levels are limited, leaving beneficiaries with relatively high copayments (Jeong 2011). Autor et al (2005) found that health returns to education were increasing in the 1980s and 1990s as earnings returns to education were also increasing. Previous studies that controlled income in estimating the effect of education on health, however, find that education coefficients remain significant (Smith 2007).…”
Section: Theoretical Explanations For How Education Affects Healthmentioning
confidence: 99%